2015
DOI: 10.1371/journal.pgen.1005637
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic and Intronic Mutations in TSC1/TSC2 Explain the Majority of TSC Patients with No Mutation Identified by Conventional Testing

Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant tumor suppressor gene syndrome due to germline mutations in either TSC1 or TSC2. 10–15% of TSC individuals have no mutation identified (NMI) after thorough conventional molecular diagnostic assessment. 53 TSC subjects who were NMI were studied using next generation sequencing to search for mutations in these genes. Blood/saliva DNA including parental samples were available from all subjects, and skin tumor biopsy DNA was available from six subjects. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
273
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(298 citation statements)
references
References 53 publications
15
273
0
10
Order By: Relevance
“…We demonstrate germline and somatic mutations 1) in TSC2 from non-TSC patients and 2) associated with HME. Our remaining cases with germline loss-of-function mutations may also contain “second hit” mutations that could represent large-scale CNVs undetectable by targeted sequencing, mutations in genes not included in our panel or in introns (Tyburczy et al, 2015a), or mutations below our detection limit.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate germline and somatic mutations 1) in TSC2 from non-TSC patients and 2) associated with HME. Our remaining cases with germline loss-of-function mutations may also contain “second hit” mutations that could represent large-scale CNVs undetectable by targeted sequencing, mutations in genes not included in our panel or in introns (Tyburczy et al, 2015a), or mutations below our detection limit.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to study genotypephenotype associations in a larger cohort of mosaic TSC patients, to determine whether these individuals are more likely to have specific types of pathology, as has been suggested previously. [25][26][27][28] Our cohort consisted of 40 individuals with a de novo mutation (12 TSC1, 28 TSC2), 12 individuals from 8 different families and 12 individuals (5 TSC1, 7 TSC2) for whom we did not have access to parental DNA. Familial TSC cases are reported to have a milder phenotype than sporadic TSC cases, although ascertainment bias cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite our efforts to also discover somatic mutations in our data, our analysis was limited by both the read depth in our study, where only variants with an allele frequency of ∼ 0.10 or higher would be detected, and also by the availability of only DNA from whole blood, in which the mutation may not even be present. Results from a study of somatic mutations in tuberous sclerosis complex showed that a majority of the patients with somatic mosaicism had an allele frequency <0.10 in blood [Tyburczy et al, 2015].…”
Section: Discussionmentioning
confidence: 99%